What is the Impact of Online Hate? - Doyon, Natasha (The Canadian Art Teacher / Enseigner les arts au Canada, 2024)
This is an arts-based action research (ABAR) project on how online/offline hate speech impacts new immigrant and refugee youth. Using a non-experimental qualitative arts-based approach, the youth participants developed digital literacy skills to create alternative narratives by transforming online images, text, and symbols into comics as new narratives. By working within a feminist and critical theoretical framework this project aimed to amplify the marginalized voices of youth through participatory art workshops, skill building, group discussions, and semi-structured interviews. In order to diffuse systemic inequalities and racism this research aims to build bridges between youth’s engagement with social media and their embodied knowledge towards fostering a new sense of belonging in their online/offline communities.